A Novel Ultrafast Rechargeable Multi‐Ions Battery. Issue 16 (15th February 2017) - Wang, Shuai; Jiao, Shuqiang; Tian, Donghua; Chen, Hao‐Sen; Jiao, Handong; Tu, Jiguo; Liu, Yingjun; Fang, Dai‐Ning
Abstract : An ultrafast rechargeable multi‐ions battery is presented, in which multi‐ions can electrochemically intercalate into graphite layers, exhibiting a high reversible discharge capacity of ≈100 mAh g −1 and a Coulombic efficiency of ≈99% over hundreds of cycles at a high current density. The results may open up a new paradigm for multi‐ions‐based electrochemical battery technologies and applications.